Discovery of a Potent RIPK3 Inhibitor for the Amelioration of Necroptosis-Associated Inflammatory Injury - Xia, Kaijiang; Zhu, Fang; Yang, Chengkui; Wu, Shuwei; Lin, Yu; Ma, Haikuo; Yu, Xiaoliang; Zhao, Cong; Ji, Yuting; Ge, Wenxiang; Wang, Jingrui; Du, Yayun; et al. (Frontiers in Cell and Developmental Biology, 2020)
Necroptosis is a form of regulated necrosis that requires the activation of receptor-interacting kinase 3 (RIPK3 or RIP3) and its phosphorylation of the substrate MLKL (mixed lineage kinase domain-like protein). Necroptosis has emerged as important cell death involved in the pathogenesis of various diseases including inflammatory diseases, degenerative diseases, and cancer. Here, we discovered a small molecule Zharp-99 as a potent inhibitor of necroptosis through blocking the kinase activity of RIPK3. Zharp-99 efficiently blocks necroptosis induced by ligands of the death receptor and Toll-like receptor as well as viral infection in human, rat and mouse cells. Zharp-99 strongly inhibits cellular activation of RIPK3 and MLKL upon necroptosis stimuli. Zharp-99 directly blocks the kinase activity of RIPK3 without affecting RIPK1 kinase activity at the tested concentration. Importantly, Zharp-99 exerts effective protection against TNF-α induced systemic inflammatory response syndrome in the mouse model. Zharp-99 displays favorable in vitro safety profiles and in vivo pharmacokinetic parameters. Thus, our study demonstrates Zharp-99 as a potent inhibitor of RIPK3 kinase and also highlights its potential for further development of new approaches for treating necroptosis-associated inflammatory disorders.